The Byzantine Hierarchal Divine Liturgy in Arsenij Suxanov’s Proskinintarij: Text, Translation, and Analysis of the Entrance Rites. By Vassa Larin - Wybrew, Hugh (The journal of theological studies, 2012)
Vassa Larin, a nun of the Russian Orthodox Church Abroad, teaches liturgy at the Institute for Liturgical Studies in the Faculty of Catholic Theology in the University of Vienna. Born in the United States, she was present as a child at the arrival of the local Metropolitan at her family’s parish church. The steps of the church were covered with flowers and the clergy were lined up. As soon as the Metropolitan’s limousine appeared, the church bells began to ring. Welcomed with incense and chant, the Metropolitan was vested in his mantle and entered the church. Rugs embroidered with an eagle were placed wherever he was to stand.